Menelusuri Konsep Pemikiran John Calvin Tentang Manusia dan Relevansinya Terhadap Transformasi Sosial - Rerung, Alvary Exan; Yohanis, Santi (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. This article is a study of John Calvin's concept of thought about humans. By drawing on and analyzing John Calvin's thoughts, the author believes that the background of John Calvin's life needs to be explained comprehensively in order to understand his theology about humans. The background of the life in question includes: the background of Calvin's life, the influence of philosophical schools on the formation of Calvin's theology and the controversy over his life which makes many people wonder. By using literature study approach, the author examines it analytically and methodically and obtains three points that can be of actual relevance to social transformation efforts in Indonesia. First, the social human that Calvin meant was a human who always prioritizes an attitude of hospitality. Second, social humans are humans who abandon the tendency to prioritize individualistic attitudes. Third, social people are people who continue to fight for Indonesia as a